Valor prognóstico da redução da Pressão Diastólica Arterial Pulmonar nos pacientes submetidos à Valvoplastia Mitral Percutânea - Igor Ferreira de Sales (2023)
Introduction: The presence of pulmonary hypertension (PH) is one of the main determinants of long-term cardiovascular outcomes in patients with rheumatic mitral stenosis. Percutaneous mitral valvuloplasty (PMV) with valve opening causes an immediate reduction in pulmonary arterial pressure. However, the prognostic value of reducing pulmonary arterial pressure after the procedure is not yet well defined. Objective: To identify the value of the drop in pulmonary arterial pressure immediately after PMV in predicting long-term adverse events. Methods: A total of 398 consecutive patients who underwent PMV in a reference hospital were eligible for the study. Only 10 patients (2.5%) were lost to follow-up and therefore excluded from the analyses. The 388 patients analyzed underwent echocardiography, brain natriuretic peptide (BNP) measurement and cardiac manometry of left and right chambers before and after PMV. Shortly after discharge, they were followed up in a specialized cardiology outpatient clinic. Adverse events were defined as a combination of cardiovascular death and the need for surgery for mitral valve replacement. Results: During the mean follow-up of 3.6 years, 109 patients (28%) presented the combined outcome of cardiovascular death or mitral valve replacement. The patients who presented the outcomes were notably older and more symptomatic than those in the control group. The echocardiographic scores of patients with events were higher, as was the degree of tricuspid insufficiency, indicating more advanced disease. After PMV, patients in the group that presented events maintained higher mean pulmonary arterial pressure compared to the control group, as well as a greater transpulmonary gradient. In the final multivariate model, the predictors of long-term adverse events were signs of right heart failure before PMV [2.619 (1.537-4.464)], final valve area after PMV [0.097 (0.039-0.243)], elevated mean transmitral gradient after PMV [1.080 (1.003-1.163)], severe mitral regurgitation after the procedure [3.151 (2.195-4.522)], the degree of reduction in diastolic pulmonary pressure after PMV [0.962 (0.927-0.998)], the degree of increase in atrial compliance left after PMV [0.967 (0.941-0.995)]. Conclusion: This study demonstrated that the rapid decrease in pulmonary artery diastolic pressure subsequent to PMV serves as a reliable predictor of long-term cardiovascular events. Furthermore, the immediate improvement in left atrial compliance, another invasive hemodynamic parameter, appears as a predictive factor for events. Furthermore, traditionally recognized post-procedure variables that indicate procedural success continued to be important predictors of outcome.